How Do Amounts, Composition, and Quality of Accruals Differ for Physical versus Knowledge Firms? - Iqbal, Aneel; Srivastava, Anup (The Accounting Review, 2026)
ABSTRACT We examine whether accrual accounting loses relevance with the rise of knowledge firms. Investigating a large sample of U.S. firms from 1990 to 2022, we compare magnitudes, components, quality, and pricing of accruals across knowledge- and physical-asset firms. Knowledge firms report lower accruals and poorer accrual quality, but the gap is concentrated in small knowledge firms. Their low-quality accruals reflect largely innate, volatile, uncertain, early-stage operations, not discretionary reporting. As these firms scale, their accrual magnitudes and quality converge to those of similarly sized physical firms. These life-cycle dynamics reconcile the 1990s decline and post-2000 improvement in aggregate accrual quality through offsetting “new-list” and “maturation” effects. Accrual accounting remains decision-useful in a knowledge economy, as the market prices, and thus seems to recognize, the information risk emanating from poor accrual quality, especially for knowledge firms. JEL Classifications: M13; M41.